2021
DOI: 10.1007/s40839-020-00131-5
|View full text |Cite
|
Sign up to set email alerts
|

Religious education for ecological sustainability: an initial reality check using the example of everyday decision-making

Abstract: There is a widely accepted consensus that religious education, together with all other school subjects, should contribute to the goals of education for sustainable development. As a result, theoretical models have been developed to profile what the specific contributions of religious education might be. However, the question whether religious education can achieve the intended goals has not yet been researched in more detail. More fundamentally, to be able to formulate realistic goals involves the clarificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…Eco-Theology can create religious awareness to embolden respect for nature (REEP), 1994, Hammelt, 2012. Altmeyer (2021) exposed that "ecological issues are regarded by many as religious and spiritual questions and can therefore be addressed in a focused way through religious education". The knowledge of religious stewardship, which suggests taking obligation, goes for both religious and non-religious learners, could be mostly encouraging.…”
Section: Eco-theology Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Eco-Theology can create religious awareness to embolden respect for nature (REEP), 1994, Hammelt, 2012. Altmeyer (2021) exposed that "ecological issues are regarded by many as religious and spiritual questions and can therefore be addressed in a focused way through religious education". The knowledge of religious stewardship, which suggests taking obligation, goes for both religious and non-religious learners, could be mostly encouraging.…”
Section: Eco-theology Reviewmentioning
confidence: 99%
“…Research Analysis of the responses of 14-to 16-year-old students at secondary schools in Germany and Austria by Altmeyer (2021) revealed that ecological issues are considered by sundry as religious and spiritual questions and can therefore be lectured in a fixated way through religious education. The concept of religious stewardship, which suggests taking responsibility and takes on both religious and non-religious learners, could be predominantly auspicious.…”
Section: Eco-theology Reviewmentioning
confidence: 99%
“…Typical etiological questions were avoided (e.g., Basel et al, 2013Basel et al, , 2014, and instead comprised of three scenarios: 'Christmas for non-Christians', addressing arguments over whether religious festivals should be celebrated by non-adherents to that faith; 'What's growing?' addressing the biological distinction between plants and fungi; 'A zoo near you', addressing the socio-scientific issue of the ethics of zoos, including the religious notion of stewardship (see Altmeyer, 2021). They are referred to as the Christmas, Stems and Zoos scenarios.…”
Section: The Instrumentmentioning
confidence: 99%
“…ere is a potential development of human beings, and the task of educators is to create conditions for the development of human potential, like a gardener, so that it can be developed in a predetermined process and grow naturally like a plant [16].…”
Section: Introductionmentioning
confidence: 99%
“…It draws on the concept of ecological restoration and holds that people must learn to respect and obey nature. There is a potential development of human beings, and the task of educators is to create conditions for the development of human potential, like a gardener, so that it can be developed in a predetermined process and grow naturally like a plant [ 16 ]. The fatal aspect of gardening education is that they see human potential as something already existing, like oil at the bottom of the sea that can burst out of itself once it breaks through the surface.…”
Section: Introductionmentioning
confidence: 99%